LITERASI DIGITAL (Telaah Administrasi Persiapan Pembelajaran) - Nuraini Nuraini (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Digital learning itself is a system that can help students learn more widely, more varied, or more. With the support provided, students can conduct their learning activities anywhere, anytime, regardless of location, time, or distance. The teaching materials offered can also be more diverse than just oral forms, such as: Text, images, visuals, audio, movement, and so on. Digital learning requires interactive communication between students and teachers using information and communication technology. For example, the use of computer media with the internet, smartphones with various applications, video, telephone or fax. Literacy learning planning teachers design learning designs on certain subjects or materials that are adjusted to the characteristics of the class. For this reason, before designing, teachers should make observations that can be strengthened by interviews to find out the condition of the class and analyse the needs of students. During the teaching and learning process, the teacher is not only the one who transfers knowledge but the teacher must also be able to provide the means for students to form their thoughts as well as their attitudes. In addition, teachers must have a strong desire to carry out their duties, a sense of responsibility for their position, and interest in the plans they make in the form of lesson plans. In this evaluation, teachers use various methods and instruments to measure the extent to which students understand the basic concepts of digital literacy, such as digital safety, online ethics and information management. In addition, the evaluation also includes assessing students' practical skills in using software, applications and digital tools, such as information retrieval, data processing and online communication